Correction: Chemical fixation of CO2 into cyclic carbonates by azo-containing Schiff base metal complexes. (19th August 2015) - İkiz, Mesut and İspir, Esin and Aytar, Emine and Ulusoy, Mahmut and Karabuğa, Şemistan and Aslantaş, Mehmet and Çelik, Ömer
Abstract : Correction for 'Chemical fixation of CO2 into cyclic carbonates by azo-containing Schiff base metal complexes' by Mesut İkiz et al., New J. Chem., 2015, DOI: ; Web:10.1039/c5nj00571j .